(untitled) (Research, Society and Development, 2022)
For decades, non-renewable energy resources have been used indiscriminately, but their slow depletion and extremely harmful impacts on the environment have shifted the focus to sustainable and renewable energy sources. Among the renewable energy sources, biofuel cells are defined as devices that convert chemical energy present in chemical bonds into electrical energy. Biocells are classified into two broad categories of enzymatic fuel cells, which employ enzymes as biocatalysts, and microbial fuel cells, which use microorganisms as biocatalysts. An important requirement in the functioning of a biofuel cell is the transfer of electrons from inside an active site of an enzyme to the outside, as the electrodes being solid cannot penetrate the enzymes. A wide range of molecules can be used as electrochemical mediators, some with high toxicity and many non-toxic fungal substances having an enormous potential to be used as electrochemical mediators. In this work, the fungal pigment bikaverin was compared to the synthetic dye Congo red, in order to obtain the best energy-optimizing molecule in an enzymatic fuel cell. Congo red presented a higher current density of 273 mA.cm-2 compared to bikaverin, 230 mA.cm-2, but because it presents a more stable chronoamperometric graph and does not have high toxicity, the fungal biopigment proved to be the best option for optimization. on the potential of energy generated in an enzymatic fuel cell.